Perception of risk of musculoskeletal disorders among Brazilian dental students - Garcia, Patrícia Petromilli Nordi Sasso [UNESP] (2013)
The aim of this study was to compare the mean scores of perceived risk factors for the development of musculoskeletal disorders in dental students presently pursuing work/study, according to gender, course series, and the presence of pain/discomfort. The participants were 348 students from the undergraduate course in dentistry at a Brazilian public university. The instrument on work-related factors that could contribute to osteomuscular symptoms and part of the Nordic questionnaire were used. The psychometric properties of the first instrument were estimated. A multivariate analysis of variance (MANOVA) revealed that the instrument had a tri-factorial structure (s2 retained: 62.72 percent). The retained factors were repetitiveness, work posture, and external factors. The internal consistency and reproducibility were adequate (α=0.746 to 0.873; p=0.729 to 0.940). Lower mean scores of perceived external factors were observed for the male participants, as well as lower scores in the three dimensions of the instrument for first-year students of the course and for those who did not report pain/discomfort in the neck, feet, and ankles. The authors concluded that the perception of risk factors for musculoskeletal disorders reported in the work/study environment of dental students was significantly related to gender, the course series, and the presence of pain/discomfort.